Unfaithful [videorecording (DVD)] - Lyne, Adrian; Gere, Richard, 1949-; Lane, Diane; Martinez, Olivier, 1966- (20th Century Fox Home Entertainment, 2002)
When a chance encounter with a sexy stranger erupts into a full-blown affair, passion becomes obsession, and the true price of betrayal takes a shattering toll.